A Date with Ruskin Bond - Dutta, Usha (THE PRIMARY TEACHER, 2009)
Ruskin Bond born in 1934 is an icon among Indian writers. He received the Sahitya Akademi Award in 1992. He was awarded the Padmashri in 1999 for contributions to children’s literature. Most of his writings show a strong influence from the social life in the hill stations at the foothills of the Himalayas, where he spent his childhood. His first novel was “The Room on the Roof”, written when he was 17. He is the author of over 300 short stories and more than 30 books for children. This article presents excerpts from a visit of the Children’s Literature team to Ivy Cottage, that has been Bond’s home since 1964.